(untitled) (African Journal of Biomedical Research, 2023)
Psychological well-being as a positive mental state defines an individual’s self-acceptance, positive connection with others, environmental mastery, autonomy, life purpose, and self-awareness, all of which improve one’s quality of life. The mental state of healthcare providers is often overlooked or given little attention in low-and middle-income countries; however, this area of exploration remains a major concern in Nigeria. This study aims to investigate whether family structure moderates the relationship between parenting styles and psychological well-being among nursing students in Imo State, Nigeria. Three hundred and thirty-eight (338) nursing students selected from two different nursing institutions in Imo State were sampled in this study. The participants’ age ranges from 18–50 years (M = 36.82 and SD = 10.46). The study adopted a cross-sectional survey design. Two research instruments were used for data collection: the Parenting Style Rating Scale (PSRS) and the Psychological Wellbeing Rating Scale (PWR). Moderated regression analysis was conducted using Process Macro version 4.1 to analyse the data. The result revealed that family structure significantly predicted psychological well-being. Also, parental styles positively and significantly predicted psychological well-being. Furthermore, family structure positively and significantly moderates the relationship between parenting styles and psychological well-being. The study emphasizes the need for adequate measures to improve the psychological well-being of nursing students by developing a grass-roots advocacy and sensitization program for student-parents or sponsors that would encourage parental involvement or participation in their child’s quality of life.